2013
DOI: 10.1021/jp3101877
|View full text |Cite
|
Sign up to set email alerts
|

A Combined NMR and DFT Study of Narrow Gap Semiconductors: The Case of PbTe

Abstract: In this study we present an alternative approach to separating contributions to the NMR shift originating from the Knight shift and chemical shielding by a combination of experimental solid-state NMR results and ab initio calculations. The chemical and Knight shifts are normally distinguished through detailed studies of the resonance frequency as function of temperature and carrier concentration, followed by extrapolation of the shift to zero carrier concentration. This approach is time-consuming and requires … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 66 publications
7
45
0
Order By: Relevance
“…S5). Other detailed NMR studies of the Knight shift and relaxation in PbTe (E g = 0.32 eV, 300 K) and Tl 2 Se (E g = 0.6 eV, 300 K) were consistent with a decrease in carrier concentration in nanoscale materials compared with bulk materials (24,25), in contrast with the behavior observed in TI nanocrystals. Furthermore, in the case of ZnTe (E g = 2.23 eV, 300 K) the 125 Te frequency shift of nanoZnTe remains unshifted relative to micrometer-sized samples (Fig.…”
Section: Resultssupporting
confidence: 56%
“…S5). Other detailed NMR studies of the Knight shift and relaxation in PbTe (E g = 0.32 eV, 300 K) and Tl 2 Se (E g = 0.6 eV, 300 K) were consistent with a decrease in carrier concentration in nanoscale materials compared with bulk materials (24,25), in contrast with the behavior observed in TI nanocrystals. Furthermore, in the case of ZnTe (E g = 2.23 eV, 300 K) the 125 Te frequency shift of nanoZnTe remains unshifted relative to micrometer-sized samples (Fig.…”
Section: Resultssupporting
confidence: 56%
“…8d) for SnTe (x=1). This is an interesting result given that the SnTe is also a p-type semiconductor (with a lower Seebeck coefficient than PbTe) and this sort of temperature dependence is usually observed for n-type semiconductors, not p-type [12,13,[20][21][22][23][24][25][26] rates, see below). At this Sn fraction the CB and VB are now overlapped, yielding an increase in the DOS at the Fermi level and a metallic character due to the E g →0 (Fig.…”
Section: Temperature Dependence Of the Nmr Spectramentioning
confidence: 79%
“…Such a resonance frequency shift is considered large for a semiconductor. Previous studies have shown that the resonance shifts of 207 Pb can extend up to 12,000 ppm (relative to tetramethyllead [19,42] by extrapolating the resonance position to the limit of zero free carriers [12,21]. If the carrier concentration (Knight shift) were the main contribution to the total shift, then we should expect the 207 Pb spectrum of x=0.60 to be more upfield (lower frequency) than the spectrum of x=0.35.…”
Section: B Nmr Spectral Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…activated T-dependence [37]. NMR in PbSe [38] and PbTe [39] has probed similar behavior. At ambient temperature, the interplay between and ℎ is constant as expressed by the conductivity but strongly varies across the Bi 2 Te 3-x Se x series.…”
Section: Resultsmentioning
confidence: 91%